Monitoring the Middle School Movement: Are Teachers In Step? - John A. Huss (Arizona State University, 2011)
A descriptive study examined the degree to which middle level teachers in grades 6-8 in three states accept the tenets of the middle school philosophy. The guiding questions were: (1) Does a cross difference in variables exist among teachers from different organizational settings or grade configurations in respect to the teacher's acceptance of the tenets of the middle school philosophy? (2) Does a cross difference in variables exist among teachers who hold different types of certification or licensure in respect to the teacher's acceptance of the tenets of the middle school philosophy? Based on the overall data, the middle school movement appears to be making steady progress. Data in this study suggest substantial teacher acceptance of the middle school philosophy across the various organizational settings. Pearson chi square values denoting significant differences across building configurations were revealed for eight of the 20 survey questions. A greater sense of uniformity existed across certification or licensure types with significant differences uncovered for four of the 20 questions.